2005
DOI: 10.1097/01.jom.0000166864.58664.29
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Chronic Health Conditions on Work Performance, Absence, and Total Economic Impact for Employers

Abstract: For all chronic conditions studied, the cost associated with performance based work loss or "presenteeism" greatly exceeded the combined costs of absenteeism and medical treatment combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
348
3
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(375 citation statements)
references
References 29 publications
15
348
3
9
Order By: Relevance
“…Two of 3 additional epidemiologic studies replicated this pattern of a stronger association with presenteeism than with absenteeism. We did not review evidence from some other epidemiologic sources because of their reliance on nonstandardized measures of mental health and presenteeism; nonetheless, they also reported an association of presenteeism with various indicators of depression (57)(58)(59)(60). The tendency of people with depression to continue to come to work despite their illness represents a hidden cost of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Two of 3 additional epidemiologic studies replicated this pattern of a stronger association with presenteeism than with absenteeism. We did not review evidence from some other epidemiologic sources because of their reliance on nonstandardized measures of mental health and presenteeism; nonetheless, they also reported an association of presenteeism with various indicators of depression (57)(58)(59)(60). The tendency of people with depression to continue to come to work despite their illness represents a hidden cost of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies, health conditions that included migraines, back or neck pain, and breathing disorders were also predictors of presenteeism (Collins, et al, 2005). Quite different from Stewart et al (2003a), Collins (2005) found that working less than 40 hours was more associated with presenteeism.…”
Section: Physical Health Conditionssupporting
confidence: 73%
“…Consistent with other demographic findings, Collins (2005) found that predictors for presenteeism included female (P=0.012), plus increasing age (P=0.000), service workers or operative type jobs (P=0.000), the presence of a chronic condition, and an increased number of chronic conditions (both at P=0.000). Consistent with other studies, health conditions that included migraines, back or neck pain, and breathing disorders were also predictors of presenteeism (Collins, et al, 2005). Quite different from Stewart et al (2003a), Collins (2005) found that working less than 40 hours was more associated with presenteeism.…”
Section: Physical Health Conditionssupporting
confidence: 73%
See 1 more Smart Citation
“…These studies typically focus on the impact of specific medical conditions, for example depression (Stewart et al 2003, Simon et al 2001, back pain (van Tulder et al 1995). Collins et al (2005) use survey data from a single US corporation to assess the cost of chronic health conditions to the firm from treatment costs and output loss from absenteeism and on-the-job productivity loss ("presenteeism"). The authors conclude that the cost of presenteeism are large and higher than the costs associated with absences.…”
Section: Introductionmentioning
confidence: 99%